Clinical value of neutrophil/lymphocyte ratio in predicting postoperative complications, lymph node positivity and prognosis in gastric cancer patients who underwent curative surgical resection - Yalav, Orcun; Topal, Ugur; Gizem Unal, Ayse (Annals of Medical Research, 2021)
Aim: In this study, we aimed to determine the clinical value of neutrophil / lymphocyte ratio (NLR) in predicting postoperative complications, lymph node positivity and prognosis in patients who underwent curative surgical resection.Material and Methods: Patients who underwent total gastrectomy for gastric adenocarcinoma between 2015 and 2018 were included in the study. Two groups, Group 1 (LowNLR) and Group 2 (HighNLR), were formed. Demographic and clinical characteristics, intraoperative and postoperative outcomes, and mean survival were compared. The value of NLR in predicting lymph node positivity and postoperative complications was evaluated at the cutoff value determined for NLR.Results: Patients were divided into two groups according to the cutoff value of 2.14. Group 1 consisted of 36 patients and Group 2 consisted of 68 patients. Female sex was higher in Group 2 (72% vs 52%) (p:0.41). Postoperative complication rates according to Clavien Dindo classification were similar (p:0.9). The number of dissected positive lymph nodes was higher in Group 2 than in Group 1 (9 vs 6) (p:0.041). Pathological stage (p:0.188), and overall survival (24.61vs21.12,p:0.206) were similar between the groups. We found NLR as a risk factor for survival in multivariate analysis (HR=0.255, 95%CI: 0.024–0.427, p:0.029). If the NLR value was less than 2.14, the patient had According to Clavien Dindo classification Grade 2 and above complications, with a sensitivity of 46.3% and specificity of 76.0%. A positive lymph node was detected with 44.26% sensitivity and 65.12% specificity. Conclusion: Preoperative high NLR is a risk factor for survival in patients with gastric cancer. High NLR is also closely associated with the risk of postoperative complications.
Keywords: Gastric cancer; neutrophil lymphocyte ratio; postoperative complication.